(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
This paper obtains a characterisation of the congruences on *-simple type A I-semigroups. The *-locally idempotent-separating congruences, strictly *-locally idempotent-separating congruences and minimum cancellative monoid congruences, are characterised.